2000
DOI: 10.1074/jbc.275.18.13974
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Determinants of α7 Nicotinic Acetylcholine Receptor Surface Expression

Abstract: Transient transfection has not been a successful method to express the ␣7 nicotinic acetylcholine receptor such that these receptors are detected on the cell surface. This is not the case for all ligand-gated ion channels. Transient transfection with the 5-hydroxytryptamine type 3 subunit cDNA results in detectable surface receptor expression. Cell lines stably expressing the ␣7 nicotinic acetylcholine receptor produce detectable, albeit variable, levels of surface receptor expression. ␣7 nicotinic acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
1
25
1
Order By: Relevance
“…Moreover, we have previously shown that an arginine (Arg 205 according to the numbering system used here) located between Ile 202 and the latter motif and conserved in all ligand-gated channel subunits is required for transport of assembled ␣7 receptors to the cell surface (31). Also in this region certain domains have been found that affect surface expression of ␣7-5HT 3 chimeric receptors (32). All these data suggest that this region, adjacent to the first transmembrane segment, constitutes a "hot spot" with potential retention/retrieval signals involved in receptor trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have previously shown that an arginine (Arg 205 according to the numbering system used here) located between Ile 202 and the latter motif and conserved in all ligand-gated channel subunits is required for transport of assembled ␣7 receptors to the cell surface (31). Also in this region certain domains have been found that affect surface expression of ␣7-5HT 3 chimeric receptors (32). All these data suggest that this region, adjacent to the first transmembrane segment, constitutes a "hot spot" with potential retention/retrieval signals involved in receptor trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular processes that control the number of functional membrane ␣7 nAChRs are not fully understood. The normal delivery of ␣7 receptors from intracellular pools to the surface is clearly an important but not well defined process (Dineley and Patrick, 2000), and it is likely that, at least for this nAChR subtype, trafficking may depend on neuronspecific factors involved in the membrane targeting of proteins (Kassner and Berg, 1997;Sweileh et al, 2000). Indeed, during assembly in the endoplasmic reticulum, palmitoylation at cysteine residues in the intracellular loop of the ␣7 subunit is critical for surface receptor expression and fails to occur in certain nonneuronal cells (Drisdel et al, 2004).…”
Section: Cellular Mechanisms Of ␣7 Nachr Regulationmentioning
confidence: 99%
“…The pellet was suspended in p-aminobenzamidine-free HEPES buffer, incubated at room temperature for 15 min, and centrifuged once again for 15 min at 4°C (40,000g). Marks et al (1992) and Dineley and Patrick (2000) with slight modifications. Samples containing rat brain membranes (300 -350 g of protein), the test compound and 1 nM [ 3 H]␣-bungarotoxin (60 Ci/mmol) were incubated in a final volume of 250 l for 1 h at 37°C.…”
Section: For [mentioning
confidence: 99%